Manajemen Kualitas Aset Produktif Dan Pengaruhnya Terhadap Laba Bank Pada Bank Perkreditan Rakyat di Indonesia - Hesti Budiwati (STIE Mandala Jember, 2021)
Managing the bank risk well are very needed so that the bank can operate smoothly. One of the important bank risk to managed well is bank asset quality risk. The banks are required to be careful and wiser in manage these asset quality risk. The object of this study is to obtain evidence of the effect of productive asset quality management on bank profit. The empirical studies conducted on rural banks in Indonesia. As the independent variable is productive asset quality consist of classified productive asset, productive asset quality and non-performing loan, while as the dependent variable is bank profit measured by return on asset. Return on asset of 89,6% explained by classified productive asset, productive asset quality and non-performing loan. While the rest return on asset of 10,4% effect by other variables that not examined in this study. Keywords: Classified Productive Asset, Productive Asset Quality, Non-performing Loan, Return on Asset.